The day-to-day variability in the mesosphere and lower thermosphere in low latitudes: A study using MF radar. Issue 1 (1st January 2023) - Gaikwad, H.P.; Fadnavis, S.; Gurav, O.B.; Bhosale, J.L.; Sharma, A.K.; Patil, P.T.; Ghodpage, R.N.; Sutar, M.M.; Chavan, G.A.; Birajdar, A.T.; Shetti, D.J.
Abstract: This study presents the analysis of planetary waves (PWs) using daily mean wind velocities for four years (August 2013 to July 2017) of continuous measurements using MF radar over the low latitude Indian region Kolhapur (16.8° N; 74.2° E). The MF radar at Kolhapur was upgraded in 2013. These are the first results of PWs after the upgradation of MF radar. The seasonal and intra-seasonal variabilities of East-West (EW) traveling PWs in the MLT region have been studied. In the present work, the data was analyzed to study the waves with various periodicities (e.g. 3–4, 5–8, 15–17, and 30–60 days). The 3.5 day [Ultra-Fast Kelvin (UFK)] wave shows semiannual variability with burst like wave activity observed during the summer months and December solstice. In addition, it is observed to be stronger in the spring equinoctial period. A strong semiannual oscillation (SAO) has been observed in a 6.5-day wave with peaks near the equinoxes. Similar to SAO over the low latitude MLT region, the wave activity is stronger in April/May than in September/October. The 6.5-day waves are observed to be stronger when the background mean wind is westward. From the analysis, it has been seen that the period before and after the equinoctial period is favorable for the 6.5-day wave propagation. The 16-day wave has no significant seasonal dependence; instead, the waves spread to almost all seasons. The Madden-Julian Oscillations (MJOs) have been observed to be propagating with an average wind speed of ∼ 5 m/s when the background mean wind is eastward. The occurrence of MJO is observed during the summer and winter months. These results are the first of their kind in two aspects: first, they show the PWs with enhanced altitude coverage covering up to 110 km, and second, they show the PWs not contaminated due to equatorial electro jet influence.